PENGARUH LITERASI KEUANGAN DAN GAYA HIDUP TERHADAP KESIAPAN PENSIUN PEGAWAI LPP RRI JAMBI - Regina Lastri; Rike Setiawati; Asep Machpudin (Jurnal Manajemen Terapan dan Keuangan, 2021)
In working, indvidu will go through some stages where in the final stages of retirement. It is necessary to prepare well for retirement because the income that is earned is no longer the same as working while there is still a need to be met and may be increased. This study is aimed at understanding the impact of financial literacy and lifestyle towards the ready retirement of LPP RRI Jambi employees. The study uses a quantitative approach. The sample sampling method uses the saturated sample. The number of samples in this study amounted to 57 respondents. The data used is primary data obtained through a questionnaire on a likert scale. The method of data analysis in this study employs PLS (partial least square) using smart PLS 3.0 software. The results of this study indicate that financial literacy has a significant positive effect on retirement readiness and lifestyle has a negative effect on retirement readiness.